Refractory Hand Ulceration: A Case of Chronic Ulceration and Sporotrichoid Spread in a Fish Tank Hobbyist following Mycobacterium marinum Infection - D. Salik; V. Del Marmol (Karger Publishers, 2011)
We report the case of a 35-year-old man with a chronic ulceration of the hand in whom an infection with Mycobacterium marinum was diagnosed. Clarithromycin and doxycycline were prescribed, resulting in a slow resolution of the ulceration. M. marinum is a nontuberculous mycobacterium that causes skin lesions such as nodules, ulcerations, and sporotrichoid spread, but may also be responsible for osteoarticular lesions. In this case report, we discuss the clinical characteristics of this condition, as well as its diagnostic methods and treatments.